An Analysis of Students’ Ability in Writing Application Letter at Tenth Grade Students of SMAN 2 Muaro Jambi - Wenti, Sisra; Fitri, Nurul; Munawwaroh, Khidayatul (Universitas Batanghari Jambi, 2025)
This research aimed to analyze the ability of tenth-grade students at SMAN 2 Muaro Jambi in writing application letters, with a specific focus on their content writing skills. This study employed a quantitative descriptive method. The subjects of the research were 35 tenth-grade students at SMAN 2 Muaro Jambi. The data collection technique used was a writing test. The research utilized descriptive statistics to analyze the data. The results show that 29% of students demonstrated very high ability, 20% high ability, 14% moderate ability, and 37% low ability in overall application letter writing. Regarding content specifically, 11% of students showed very high ability, 17% high ability, 0% moderate ability, and 72% low ability. The study concludes that while students showed varied abilities in overall application letter writing, a significant majority demonstrated low ability in writing the content of application letters.